Cerebral palsy with dislocated hip and scoliosis: what to deal with first? - Helenius IJ; Viehweger E; Castelein RM (Germany, 2022)
PURPOSE:
Hip dislocation and scoliosis are common in children with cerebral palsy (CP). Hip dislocation develops in 15% and 20% of children with CP, mainly between three and six years of age and especially in the spastic and dyskinetic subtypes. The risk of scoliosis increases with age and increasing disability as expressed by the Gross Motor Function Score.
METHODS:
A hip surveillance programme and early surgical treatment have been shown to reduce the hip dislocation, but it remains unclear if a similar programme could reduce the need for neuromuscular scoliosis. When hip dislocation and neuromuscular scoliosis are co-existent, there appears to be no clear guidelines as to which of these deformities should be addressed first: hip or spine.
RESULTS:
Hip dislocation or windswept deformity may cause pelvic obliquity and initiate scoliosis, while neuromuscular scoliosis itself leads to pelvic obliquity and may increase the risk of hip dislocation especially on the high side. It remains unclear if treating imminent hip dislocation can prevent development of scoliosis and vice versa, but they may present at the same time for surgery. Current expert opinion suggests that when hip dislocation and scoliosis present at the same time, scoliosis associated pelvic obliquity should be corrected before hip reconstruction. If the patient is not presenting with pelvic obliquity the more symptomatic condition should be addressed first.
CONCLUSION:
Early identification of hip displacement and neuromuscular scoliosis appears to be important for better surgical outcomes.